Usability evaluation of non-immersive virtual reality: Identifying the characteristics for creating and effective usability assessment tool. - Lau, Siew Yung; Chen, Chwen Jen (2009)
Usability evaluation of virtual environments (VE) remains a research challenge for human factors specialists. Although there are numerous research studies on usability evaluation of VEs, most of these studies focus on the usability engineering of immersive virtual reality (VR), which concern with its unique characteristics such as immersion, wayfinding, navigational techniques, object selection, manipulation, and etc. Indeed, there are limited studies that emphasise on usability evaluation of the alternative type of VR, which is non-immersive VR, also known as Desktop VR. Several researchers have attempted to use conventional usability evaluation methods that are designed for two-dimensional Graphic User Interface (GUI) in the usability evaluation for non-immersive VR. However, such methods are inappropriate as non-immersive VR involves the use of real-time interactive three-dimensional representation. As such, this paper looks into the characteristics which distinct the evaluation of non-immersive VR from the conventional 2D interfaces and immersive VR. This aims to provide insight for future research on usability of non-immersive VR and sheds lights on the process of developing a more comprehensive and effective usability assessment tool.